2017
DOI: 10.3390/su9071201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Agronomic Impacts on Yield-Scaled N2O Emission from Wheat and Maize Fields in China

Abstract: Contemporary crop production faces dual challenges of increasing crop yield while simultaneously reducing greenhouse gas emission. An integrated evaluation of the mitigation potential of yield-scaled nitrous oxide (N 2 O) emission by adjusting cropping practices can benefit the innovation of climate smart cropping. This study conducted a meta-analysis to assess the impact of cropping systems and soil management practices on area-and yield-scaled N 2 O emissions during wheat and maize growing seasons in China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 49 publications
3
5
0
Order By: Relevance
“…Fig. 6) were consistent with findings in metaanalyses by Akiyama et al (2010) and Gilsanz et al (2016) that NI was more effective in reducing N 2 O emissions from a given land use when emissions were greater. These greater reductions were attributed in the model to heavy rainfall several days after application in 2016 ( Fig.…”
Section: Spring Slurry Applicationsupporting
confidence: 88%
See 3 more Smart Citations
“…Fig. 6) were consistent with findings in metaanalyses by Akiyama et al (2010) and Gilsanz et al (2016) that NI was more effective in reducing N 2 O emissions from a given land use when emissions were greater. These greater reductions were attributed in the model to heavy rainfall several days after application in 2016 ( Fig.…”
Section: Spring Slurry Applicationsupporting
confidence: 88%
“…In a meta-analysis of field experiments conducted for 2008, Akiyama et al (2010) found average reductions of 38 ± 6 % in N 2 O emissions from NI, with some variation attributed to land use type and emission rates. Similar average reductions of 35 %-40 % were reported in more recent meta-analyses by Ruser and Schulz (2015), Gilsanz et al (2016), and Gao and Bian (2017). However the magnitudes of these reductions are uncertain because they vary with the rate and timing of fertilizer or slurry application, with land use and ecosystem type (Akiyama et al, 2010), and with application method (Zhu et al, 2016).…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Previous studies showed that the N fertilizer application rate was one of the key factors influencing soil N 2 O production [26]. Meanwhile, N fertilizer application rate also had considerable impacts on crop yield [41]. Therefore, it is very important to determine a reasonable rate of N fertilizer application in the Sichuan Basin after forestland conversion to cropland, which can simultaneously achieve high yield and mitigate soil N 2 O emission.…”
Section: Effects Of Land Use Conversion On Soil N 2 O Emissions and Ymentioning
confidence: 99%